Novel Porcine Model of Coronary Dissection Reveals the Impact of Impella on Dissected Coronary Arterial Hemodynamics - Kariya, Taro; Yamada, Kelly P.; Bikou, Olympia; Tharakan, Serena; Miyashita, Satoshi; Ishikawa, Kiyotake (Frontiers in Cardiovascular Medicine, 2020)
Background. Coronary arterial dissection (CAD) sometimes accompanies unstable hemodynamics and requires mechanical cardiac support. Meanwhile, mechanical cardiac support may influence coronary hemodynamics in CAD. No study has examined the impact of Impella left ventricular (LV) support on CAD. Materials and Methods. CAD was induced in eight Yorkshire pigs by injuring the left anterior descending artery (LAD) using a 0.018-inch stiff guidewire and/or deep engagement of a blunt-cut coronary guiding catheter. After the creation of CAD, hemodynamic parameters, coronary pressure and flow as well as coronary angiograms were acquired before and after maximum LV support using the Impella CP. Result. CADs with a large flap were successfully created by deep engagement of a blunt-tip guiding catheter with forceful contrast injection. One animal (#8) exhibited Thrombolysis in Myocardial Infarction (TIMI)-1 flow, while the others (animal #1-#7) showed TIMI-2/3 flow. In TIMI-2/3 animals, maximal Impella support increased mean coronary pressure (108.4±22.5 to 124.7±28.0 mmHg, P<0.001) with unchanged mean coronary flow velocity (63.50±28.66 to 48.32±13.30 cm/s, P=0.17) of the LAD distal to the dissection. The LV end-diastolic pressure (20.6±6.6 vs 12.0±3.4 mmHg, P =0.032), LV end-diastolic volume (127±32 vs 97±26 mL, P =0.015), stroke volume (68±16 vs 48±14 mL, P =0.003), stroke work (5,744±1,866 vs 4,424±1,650 mmHg·mL, P =0.003), and heart rate (71.4±6.6 vs 64.9±9.3 /min, P =0.014) were all significantly reduced by Impella support, indicating effective unloading of the LV. In the TIMI-1 animal (animal #8), maximal Impella support resulted in further delay in angiographic coronary flow and reduced distal coronary pressure (22.9 to 17.1 mmHg), together with increased false-lumen pressure. Conclusion: Impella support effectively unloaded the LV and maintained the hemodynamics in a novel porcine model of CAD. Coronary pressure distal to the dissection was increased in TIMI-2/3 animals after Impella support, but decreased in the animal with initial TIMI-1 flow.